Pembuatan Briket dengan Menggunakan Limbah Bonggol Jagung di Desa Tangga Batu - Putri Fazirah Rahman; Indah silviani putri; Eros Anggara Lubis; Firza Rio Akbar; Tarfin Zega; Tirta Wahidani; Aulia Juanda Djaingsastro (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research was carried out using a qualitative method through a direct survey conducted in Tangga Batu Village. The main goal of this study is to utilize corn cob waste into an alternative fuel product in the form of briquettes that is more environmentally friendly. Corn cobs are one of the abundant agricultural wastes, but they are often not used optimally. Through simple innovations, this waste can be processed into alternative energy sources that have economic value while having added value for the surrounding community. The process of making briquettes begins with the preparation of equipment which includes a kiln, mold, drying container, mash tool, strainer, and scale. The main ingredient is corn cobs that are first dried in the sun for 3–4 days to reduce the moisture content by 10–20%. Additional materials used are tapioca flour as an adhesive, small amounts of diesel, and water. The next stage is to compose the corn cobs in the burning pit for 20–30 minutes until they become charcoal. The charcoal is then scraped using a simple tool and sifted to separate the fine and rough parts. The fine charcoal is mixed with a starch adhesive from tapioca flour, then molded using a simple mold and compacted through a pressing process to produce good quality briquettes. Next, the briquettes are dried in the sun for 2-3 days until they are completely dry and ready to be used as fuel instead of wood or kerosene. The results of the study show that corn cob waste has great potential to be used as an alternative fuel. In addition to being environmentally friendly, these products also contribute to reducing dependence on fossil fuels.